Recovery of Nickel from Reformer Catalysts of Direct Reduction, Using the Pressurized Dissolving Method in Nitric Acid - Abrar, B.; Halali, M.; Pourfathi, A. (Engineering, Technology & Applied Science Research, 2016)
In the process of direct reduction of iron pellet and production of sponge iron, NiO/Al2O3 act as a catalyst for the generation of carbon monoxide and hydrogen by vapor and natural gas. As an expensive material used in MIDREX method for steel units, this type of catalyst has major environmental problems after accumulation. The steel industry in Iran hopes to employ the MIDREX technique for the 80 percent of the 50 million tons of steel. Thus, the problem of spent catalysts will become a serious environmental challenge. Through the hydrometallurgy method, the present study investigates a possible solution to the problem of catalyst depot (due to heavy metals such as nickel) via nickel recovery, which may increase the possibility of selling or re-using the precious and expensive metal. The present research studied the Nickel recovery from spent catalysts of NiO/Al2O¬3 used in reduction gas reliefs of the production of sponge iron unit. In this study, the parameters of temperature, concentration, time and Rpm were studied using pressurized dissolving method. 100% efficiency was achieved at 140 °C for 120 minutes, nitric acid concentration of 1.5 mm, Rpm of 600 and 40 s/l 40 grams per liter.